Designing web APIs : building APIs that developers love - Jin, Brenda
Using a web API to provide services to application developers is one of the more satisfying endeavors that software engineers undertake. But building a popular API with a thriving developer ecosystem is also one of the most challenging. With this practical guide, developers, architects, and tech leads will learn how to navigate complex decisions for designing, scaling, marketing, and evolving interoperable APIs. Authors Brenda Jin, Saurabh Sahni, and Amir Shevat explain API design theory and provide hands-on exercises for building your web API and managing its operation in production. You'll also learn how to build and maintain a following of app developers. This book includes expert advice, worksheets, checklists, and case studies from companies including Slack, Stripe, Facebook, Microsoft, Cloudinary, Oracle, and GitHub. Get an overview of request-response and event-driven API design paradigms. Learn best practices for designing an API that meets the needs of your users. Use a template to create an API design process, scale your web API to support a growing number of API calls and use cases. Regularly adapt the API to reflect changes to your product or business. Provide developer resources that include API documentation, samples, and tools.